Guidelines on the integrated approach to development projects in borderlands - Ilcheong Yi; Faridah Nassali; Zhen Lee (United Nations Research Institute for Social Development (UNRISD), 2022)
Despite a broad agreement on the importance and necessity of an integrated approach and some meaningful development of methods and tools for an integrated approach, comprehensive, practical and concrete guidance on how to plan, implement and evaluate an integrated approachbased project (IABP) is still lacking. These Guidelines aim to fill this gap by providing knowledge and information on how to design, implement and evaluate an IABP. The Guidelines were developed to help practitioners understand the logical sequence and process of development projects that aim to achieve multiple goals (impacts), intermediate results (outcomes), and strategic objectives (long-term outcomes). They also enable deeper reflective analysis of the assumptions behind how and why changes in multiple sectors might happen as an outcome of a development project. The Guidelines can deepen understanding of stakeholders, project environment, scope, challenges, and the interdependencies of economic, social and environmental problems that the project aims to solve. Further, they systematically organize discussions among stakeholders, including project planners, implementers, beneficiaries and evaluators, to reflect on the values, perspectives and philosophies of change, development and transformation of society. The Guidelines focus on the effective development and deployment of strategies for an integrated approach, as well as the identification and uses of execution tools and techniques. This focus also reflects the recent trends in project management standards, shifting from processbased to principle-based standards. Moving beyond the focus on the processes composed of consistent and predictable practices, the Guidelines provide guiding principles to support effective integrated project management, which can produce intended outcomes rather than the deliverables alone. The target audience for these Guidelines includes planners, implementers and evaluators working on projects that have adopted an integrated approach, particularly in fragile and conflict-affected countries, borderlands or cross-border areas. Such regions usually involve cross-sectoral issues and objectives and goals related to peacebuilding (and state building in the case of some conflictaffected countries). The Guidelines may also be helpful to all international development and cooperation stakeholders who are interested in combining sectoral goals, projects and evaluation criteria at various levels of international development and cooperation processes-such as strategy building, project planning, programmes and project portfolios, and the evaluation of projects and programmes in terms of integrating the sustainable development goals (SDGs) and their targets.
Keywords: 330